Why is Germany's manufacturing industry so competitive? - Federico Foders; Manuel Molina Vogelsang (Kiel Institute for the World Economy (IfW), 2014)
The German economy has been outperforming other member countries of the European Union during the recent Great Recession and the still ongoing European debt crisis. What are the determinants of this outcome? This paper sets out to empirically analyze the trade and technology specialization and the price/cost performance of the German economy over the period 1990 - 2011. Furthermore, we apply the unit value approach to determine whether the competitiveness of German manufacturing products is related to price or quality advantage. Also, we estimate the degree of vertical specialization characterizing the German export sector in order to assess the role global value chains play in strengthening Germany's position in manufacturing. All indicators are calculated for Germany, the Republic of Korea, the People's Republic of China, Japan and the United States. Our results confirm that Germany is specialized in medium-range technology products and show that quality is the main driver of Germany's international success, that price and cost advantage determines competitiveness in some product groups and that R&D efforts have contributed to develop and maintain German competitiveness in manufactured products.
Keywords: 330